"Time in Office" of City Mayors and Economic Convergence, c. 1870-Present - Matteo Calabrese; Bas van Leeuwen (The Journal of European Economic History (JEEH), 2024)
According to various growth theories, technology is the main factor driving long-run growth and economic convergence. Yet this process is constrained by the features of a country's institutional background. In this paper, we investigate the relationship between economic convergence and countries' institutions, in particular by focusing on the duration of mayors' office terms. To this end, we built a novel institutional dataset covering 53 countries with mayors' tenures for the period c. 1870-2010. By using a rolling sample methodology with institutional thresholds based on the length of the mayors' tenures, we find, on the one hand, economic divergence between countries with similarly low levels of "time in office". On the other hand, we find a consistent process of convergence among countries with higher levels of time in office. Additionally, we argue that shorter mayoral tenures can have positive effects on economic con- vergence dynamics only for countries with good institutional funda- mentals overall.
Keywords: 330